Komunikasi Instruksional Pada Program Kesetaraan Paket C - Ari Usman; Ani Yuningsih; Ike Junita Triwardhani (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
Students in the high school equivalency program have their own uniqueness including: age, marital status, and socioeconomic status. They have experienced dropout and have not carried out learning activities for a long time. During the COVID 19 pandemic, most of the learning process takes place online, which is not easy for them. The research entitled "Instructional Communication in the High School Equivalency Program" intends to find out how the instructional communication model between tutors and students of the high school equivalency program in PKBM Patrakomala Bandung. The purpose was to analyze the interaction between tutors and students, the application of learning methods, the use of media, and the obstacles faced in the instructional communication process. This study uses a qualitative method with a case study approach. This study also uses constructivism theory from Jesse Delia. The results show that offline interactions are transactional, while online interactions are interactional. The learning methods used are: independent learning methods, assignments, lectures, and questions and answers. Tutors have full authority to determine the learning method to be used. The media used are seTARA Daring and WhatsApp groups. The obstacles encountered come from personal and situational variables of the students.